TRANSISI PEMUDA YOGYAKARTA MENUJU DUNIA KERJA: NARASI DAN PERSPEKTIF DARI SELATAN - Oki Rahadianto (Jurnal Universitas Paramadina, 2013)
AbstractThis article presents four narratives of youth transition from school to work in Yogyakarta as representative of the narratives of global South. Previous studies of youth transition are dominated by theories from Metropole/Global North which treats the Periphery/Global South only as a source of data. Instead of contending that young people is free to make choice as argued by dominant youth transition theories from Metropole, this article argues young people in Yogyakarta have to negotiate with sociocultural and structural factors surround them. Following contextual approach by White and Wyn (1998), considering the importance of family and local culture (Nilan 2011) and taking into account unequal relation between Metropole and Periphery (Connell 2007), this article shows how young people in Yogyakarta are affected by both sociocultural and structural factors to take the fast track of transition by entering job market in their early years. This article concludes by suggesting the importance of emerging narratives of young people from Global South to create plurality of voices in knowledge production especially in developing youth studies.Kata kunci: transisi pemuda, narasi selatan, sosiokultural, struktural, Yogyakarta.